Commitment to honesty - Takeshi Ojima; Shinsuke Ikeda (Osaka University, Institute of Social and Economic Research (ISER), 2025)
If dishonest behavior stems from a self-control problem, then offering the option to commit to honesty will reduce dishonesty, provided that it lowers the self-control costs of being honest. To test this theoretical prediction, we conducted an incentivized online experiment in which participants could cheat at a game of rock-paper-scissors. Treatment groups were randomly or invariably offered a hard Honesty-Commitment Option (HCO), which could be used to prevent cheating. Our between- and within-subject analyses reveal that the HCO provision significantly reduced cheating rates by approximately 64%. Evidence suggests that the commitment device works by lowering self-control costs, which is more pronounced in individuals with low cognitive reflection, rather than by an observer effect. Further analyses reveal two key dynamics. First, an individual's frequency of not using the HCO reliably predicts their propensity to cheat when the option is unavailable. Second, repeatedly deciding not to use the commitment device can become habitual, diminishing the HCO provision's effect in reducing cheating over time. This research highlights the effectiveness of honesty-commitment devices in policy design while also noting that their disuse can become habitual, pointing to a new dynamic in the study of cheating.
Keywords: C91; D91; 330; honesty; commitment; cheating; self-control; temptation; habit